Apparel design for female rock climbers: satisfactions and preferences. Issue 3 (2nd September 2017) - Johnston, Megan; Koo, Helen
ABSTRACT: This study investigated the needs and preferences women have with rock-climbing apparel to inform the design of female climbing clothing. The purpose of this study was to investigate the needs and preferences women have with rock-climbing apparel to inform the design of female climbing clothing. The results of this study can be beneficial for apparel designers when developing female climbing apparel. A total of 20 female rock climbers were interviewed using the purpose sampling method, and the results indicated that many of the subjects were not satisfied with their climbing clothing's fit, colour, and durability. The majority of interviewees (90%) were dissatisfied with the fit of their climbing pants and 85% experienced rips, holes, and split seams in their climbing pants. Many participants (80%) preferred hip length shirts to prevent the shirt from rising above their harness and 85% of subjects had a preference for tighter fitting pants.